Evaluating Rwanda Polytechnic Graduates’ Self-assessment on the Application of Soft Skills in the Workplace. - Uwayezu, Jean Claude; Nkurikiyimfura, Jean Bosco (Journal of Indonesian Scholars for Social Research, 2024)
The global appreciation for graduates possessing strong soft skills is evident, especially in the evolving nature of the engineering workplace. However, studies across the world highlighted a disconnect between employers’ expectations and the soft skills of entry-level engineers, impacting their employability. This research evaluated the Rwanda Polytechnic graduates’ self-assessment regarding the application of soft skills in the workplace. A survey on 107 graduates, after piloting soft skills and career development training, utilized a semi-structured questionnaire with a 5-point Likert scale and open-ended questions. Data analysis included descriptive statistics, graphs, and thematic analysis. The results indicated that graduates attested a high application of professional ethics and time management skills (M=4.38, SD=0.66) and communication skills (M=4.29, SD=0.70). On the other hand, professional writing, management, leadership skills, and interpersonal abilities scored a moderate level of application (3.41<M<4.20). Qualitative responses underscored the importance of soft skills in determining the level of graduates’ performance in the workplace. However, it was also emphasized that there is a need to reinforce computer literacy, collaboration skills, and time management skills. The findings of the present study underscored a meaningful connection between soft skills needed in the current and future engineering workplace and soft skills applied by the graduates. It is recommended that training institutions collaborate with industries to identify the precise soft skills needed to plan for effective training. Future researches in the form of experimental and correlational studies are recommended for getting a clear impact of specific soft skills on the graduates’ performance in the workplace.